2016
DOI: 10.5812/hepatmon.37388
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adiponectin Gene Polymorphisms With the Risk of Coronary Artery Disease in Patients With Nonalcoholic Fatty Liver Disease in a Chinese Han Population

Abstract: BackgroundCardiovascular events are an independent risk factor for nonalcoholic fatty liver disease (NAFLD), which is the leading cause of mortality in NAFLD patients. Several recent studies demonstrated that adiponectin (Ad) polymorphisms were involved in the progression of NAFLD and coronary artery disease (CAD). However, reports on the association between Ad polymorphisms and the risk of developing CAD in NAFLD patients are lacking in a Northern Han Chinese population.ObjectivesThe present study was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In addition to that, leptin receptor Q223R A allele significantly reduced the risk of NAFLD [36]. With regard to adiponectin, it was reported that rs266729 and rs2241766 G alleles were closely associated with the progression of NAFLD [37]; rs822393 (–4522 C/T) polymorphism was correlated with increased risk of NAFLD as well [38]. There is no doubt that the study of adiponectin is a hot topic among these influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, leptin receptor Q223R A allele significantly reduced the risk of NAFLD [36]. With regard to adiponectin, it was reported that rs266729 and rs2241766 G alleles were closely associated with the progression of NAFLD [37]; rs822393 (–4522 C/T) polymorphism was correlated with increased risk of NAFLD as well [38]. There is no doubt that the study of adiponectin is a hot topic among these influencing factors.…”
Section: Discussionmentioning
confidence: 99%
“…For rs266729 (− 11,377 C/G) in ADIPOQ , Du et al [ 39 ] and Zhang et al [ 40 ] found that the SNP is associated with CVD risk; Stenvinkel et al [ 41 ] revealed that rs266729 is associated with the decreased risk of CVD; Zhang et al [ 40 ], Cheong et al [ 27 ], and Chiodini et al [ 29 ] found that there is no significant association between rs266729 and CVD. For rs2241766 (+ 45 T/G), Pischon et al [ 42 ] and Jung et al [ 43 ] identified no association between rs2241766 and the risk of coronary artery disease (CAD) in patients with type 2 diabetic mellitus (T2DM); Du et al [ 39 ], Oliveira et al [ 44 ], and Mofarrah et al [ 45 ] found that there is a significant association between rs2241766 polymorphism and CAD risk; Chang et al [ 46 ] revealed that rs2241766 is associated with the decreased risk of CVD. Moreover, for rs1501299 (+ 276 G / T), Bacci et al [ 47 ] and Esteghamati et al [ 48 ] revealed that rs1501299 is associated with the decreased risk of CAD; Mohammadzadeh et al [ 38 ], however, reported that there is an association between rs1501299 and CAD risk; Foucan et al [ 49 ] found that there is no significant association between rs1501299 and CAD in patients with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that the main course of the death in patients with NAFLD is from coronary events [1618]. Cardiovascular disease accounted for about 25% deaths in patients with NAFLD [19, 20]. The pathogenesis of NAFLD is still a complex disorder and multifaceted process which remains under investigation.…”
Section: Introductionmentioning
confidence: 99%